In vitro ultrastructural changes of MCF-7 for metastasise bone cancer and induction of apoptosis via mitochondrial cytochrome C released by CaCO3/Dox nanocrystals - Kamba, Abdullahi Shafiu; Ismail, Maznah; Tengku Ibrahim, Tengku Azmi; Abu Bakar @ Zakaria, Md Zuki; Gusau, Lawal Hassan (Hindawi Publishing Corporation, 2014)
Bones are the most frequent site for breast cancer cells to settle and spread (metastasise); bone metastasis is considered to have a substantial impact on the quality of patients with common cancers. However, majority of breast cancers develop insensitivity to conventional chemotherapy which provides only palliation and can induce systemic side effects. In this study we evaluated the effect of free Dox and CaCO3/Dox nanocrystal on MCF-7 breast cancer using MTT (3-[4, 5-dimethylthiazol-2-yl]-2, 5-diphenyl tetrazolium bromide), neural red, and lactate dehydrogenase colorimetric assays while DNA fragmentation and BrdU genotoxicity were also examined. Apoptogenic protein Bax, cytochrome C, and caspase-3 protein were analysed. Morphological changes of MCF-7 were determined using contrast light microscope and scanning and transmission electron microscope (SEM and TEM). The findings of the analysis revealed higher toxicity of CaCO3/Dox nanocrystal and effective cells killing compared to free Dox, morphological changes such as formation of apoptotic bodies, membrane blebbing, and absent of microvilli as indicated by the SEM analysis while TEM revealed the presence of chromatin condensation, chromosomal DNA fragmentation, cell shrinkage, and nuclear fragmentation. Results of TUNEL assay verified that most of the cells undergoes apoptosis by internucleosomal fragmentation of genomic DNA whereas the extent of apoptotic cells was calculated using the apoptotic index (AI). Therefore, the biobased calcium carbonate nanocrystals such as Dox carriers may serve as an alternative to conventional delivery system.